2013
DOI: 10.1016/j.matbio.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Versatile role of heparanase in inflammation

Abstract: Heparanase is the only known mammalian endoglycosidase capable of degrading heparan sulfate glycosaminoglycan, both in extracellular space and within the cells. It is tightly implicated in cancer progression and over the past few decades significant progress has been made in elucidating the multiple functions of heparanase in malignant tumor development, neovascularization and aggressive behavior. Notably, current data show that in addition to its well characterized role in cancer, heparanase activity may repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 121 publications
(184 reference statements)
4
106
0
2
Order By: Relevance
“…LWT1 (60) and RMA-S-RAE-1β (25) cell lines were cultured in complete RPMI 1640 (cRPMI) media containing 10% FBS, 100 U/ml penicillin, 100 μg/ml streptomycin, 2 mM glutamax, 55 μM 2-mercaptoethanol, HEPES, and sodium pyruvate. sis, and various rare diseases (10,(46)(47)(48). We have explored the importance of heparanase production by NK cells in their infiltration into Matrigel and tumors, but it might be interesting to assess the impact of heparanase loss in other NK cell-dependent conditions such as Herpes virus infections or recruitment into inflammatory sites caused by TLR agonists or similar danger signals, in which NK cells are known to be critical in host defense (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…LWT1 (60) and RMA-S-RAE-1β (25) cell lines were cultured in complete RPMI 1640 (cRPMI) media containing 10% FBS, 100 U/ml penicillin, 100 μg/ml streptomycin, 2 mM glutamax, 55 μM 2-mercaptoethanol, HEPES, and sodium pyruvate. sis, and various rare diseases (10,(46)(47)(48). We have explored the importance of heparanase production by NK cells in their infiltration into Matrigel and tumors, but it might be interesting to assess the impact of heparanase loss in other NK cell-dependent conditions such as Herpes virus infections or recruitment into inflammatory sites caused by TLR agonists or similar danger signals, in which NK cells are known to be critical in host defense (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dengue virus nonstructural protein 1 (NS1) disrupts the endothelial glycocalyx layer on human pulmonary microvascular endothelial cells by NS1-induced expression of sialidases and heparanase (23). Furthermore, heparanase is upregulated in numerous human diseases such as cancer, diabetes, renal disease, and Alzheimer's disease (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting low molecular weight (LMW)-HA fragments accumulate and stimulate TLR2/4 and inflammatory gene expression, thereby promoting angiogenesis and cancer metastasis (7,23,24). Furthermore, active heparan sulfate (HS) fragments generated by heparanase-1 from extracellular barriers (25) and HS proteoglycan sources, such as the basement membrane perlecan (26), the cell surface syndecans (27), and glypicans (28), serve as TLR4-interacting DAMPs (29,30) (Fig. 1).…”
Section: Damps Derived From the Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…In the case of biglycan and decorin, interaction with TLRs is most likely mediated by LRRs present in the ligands (14 -16). HS and LMW-HA both activate TLR4 (25,81).…”
Section: Toll-like Receptorsmentioning
confidence: 99%